2018
DOI: 10.11607/jomi.5938
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Open-Label Study Comparing an Opioid-Sparing Postsurgical Pain Management Protocol With and Without Liposomal Bupivacaine for Full-Arch Implant Surgery

Abstract: Patients receiving an opioid-sparing postsurgical pain management protocol with liposomal bupivacaine 266 mg experienced a statistically significant reduction of postsurgical pain and clinically relevant reduction in opioid consumption. The overall incidence of treatment-emergent adverse events was comparable in patients receiving an opioid-sparing postsurgical pain management protocol with or without liposomal bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The addition of LB to a standard opioid-sparing regimen may also provide benefits in other major oral procedures, given that this has been previously demonstrated to reduce postsurgical pain after full-arch implant surgery in a randomized, open-label study. 14 The results from the present study and these past studies demonstrate y One patient did not provide a year of birth. z One patient did not identify as female or male.…”
Section: Discussionsupporting
confidence: 54%
“…The addition of LB to a standard opioid-sparing regimen may also provide benefits in other major oral procedures, given that this has been previously demonstrated to reduce postsurgical pain after full-arch implant surgery in a randomized, open-label study. 14 The results from the present study and these past studies demonstrate y One patient did not provide a year of birth. z One patient did not identify as female or male.…”
Section: Discussionsupporting
confidence: 54%
“…In another prospective, randomized, open-label study, conducted by Iero, et al 69 patients (n = 34 LB, n = 35 placebo) undergoing full-arch implant surgery were included. The authors concluded that LB 266 mg for full-arch implant placement significantly reduces post-surgical pain and clinically relevant decline in opioid consumption [11]. In both of the above mentioned studies, the adverse effects were comparable between the LB and placebo groups [10,11].…”
Section: Literature Reviewmentioning
confidence: 93%
“…(2) individuals consuming smokeless tobacco products and/or areca nut; (3) dual smoker, i.e., persons smoking tobacco along with other nicotinic products including waterpipe, bidi, and electronic cigarettes; (4) individuals who consumed alcohol habitually; (5) completely edentulous individuals; (6) individuals with maligned dentition; (7) patients suffering from medical conditions such as diabetes mellitus, renal and hepatic disorders, cardiovascular diseases, and patients suffering from the HIV infection; (8) gestation and/or nursing individuals; (9) individuals who reported to have utilized steroids, NSAIDs, probiotics, antibiotics and bisphosphonates over the past 3 months.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Furthermore, the International Congress of Implantologists (ICOI) also suggested SPP to be utilized as a diagnostic parameter for implant failure and periimplantitis [4] The numeric pain rating scale (NPRS), developed by Downie et al [5], is a valid and reliable scale often utilized to examine the SPP in subjects with musculoskeletal diseases, for instance, osteoarthritis [6]. The NPRS has also been utilized to evaluate links with dental implant surgeries [7].…”
Section: Introductionmentioning
confidence: 99%